2021
DOI: 10.7554/elife.66128
|View full text |Cite
|
Sign up to set email alerts
|

High social status males experience accelerated epigenetic aging in wild baboons

Abstract: Aging, for virtually all life, is inescapable. However, within populations, biological aging rates vary. Understanding sources of variation in this process is central to understanding the biodemography of natural populations. We constructed a DNA methylation-based age predictor for an intensively studied wild baboon population in Kenya. Consistent with findings in humans, the resulting 'epigenetic clock' closely tracks chronological age, but individuals are predicted to be somewhat older or younger than their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 99 publications
12
59
1
Order By: Relevance
“…In contrast, little signature of rank was detectable in females [15]. This result is consistent with findings that high rank in males (but not females) predicts accelerated epigenetic aging, elevated glucocorticoid and testosterone levels, and, to a lesser extent, higher mortality rates [14, 45,80]. However, it contrasts with the hypothesis of a highly consistent gene regulatory response to the social environment [66].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, little signature of rank was detectable in females [15]. This result is consistent with findings that high rank in males (but not females) predicts accelerated epigenetic aging, elevated glucocorticoid and testosterone levels, and, to a lesser extent, higher mortality rates [14, 45,80]. However, it contrasts with the hypothesis of a highly consistent gene regulatory response to the social environment [66].…”
Section: Introductionsupporting
confidence: 84%
“…To measure social bond strength, we used the dyadic sociality index (DSI, as in [45,80,101]). The DSI calculates the mean grooming-based bond strength between a focal female and her top three grooming partners in the year prior to sample collection, controlling for observer effort and dyad co-residency times (see details in the Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Another group has previously presented a blood clock for baboons based on DNA methylation profiles that were generated using a different methylation profiling platform (Reduced Representation Bisulfite Sequencing) [38]. We could not evaluate this blood clock in our data because the two genomic platforms profiled different sets of CpGs and furthermore, we did not profile blood samples in baboons.…”
Section: Discussionmentioning
confidence: 98%
“…Having exclusive control over a group of females has obvious fitness benefits, but if sustained elevated androgen production is one of the costs males must pay to do so (e.g., in geladas, harem‐holding males have higher testosterone than bachelor males across the year: Pappano & Beehner, 2014), this may help explain why multimale groups are so common. A recent study from the Amboseli Baboon Research Project found that male baboons appear epigenetically “old” for their age when they are high ranking (Anderson et al, 2021). It seems plausible that androgens may be one mechanism via which these biological changes occur.…”
Section: Discussionmentioning
confidence: 99%